2014
DOI: 10.1007/s00535-014-0959-6
|View full text |Cite
|
Sign up to set email alerts
|

Significance of exercise in nonalcoholic fatty liver disease in men: a community-based large cross-sectional study

Abstract: Performing regular exercise was associated with a reduced risk for NAFLD in men. Men with a high risk for NAFLD can be identified using questionnaires on exercise in an outpatient setting. Disease progression and further complications may be prevented by educating high-risk NAFLD patients about the importance of exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Nonalcoholic fatty liver disease is the presence of excessive fat in the liver, demonstrated by imaging modalities, such as transabdominal ultrasound, computerized tomography, and magnetic resonance imaging (3)(4)(5). It is also a diagnosis of exclusion.…”
Section: Nafld: Definitions Prevalence and Related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonalcoholic fatty liver disease is the presence of excessive fat in the liver, demonstrated by imaging modalities, such as transabdominal ultrasound, computerized tomography, and magnetic resonance imaging (3)(4)(5). It is also a diagnosis of exclusion.…”
Section: Nafld: Definitions Prevalence and Related Factorsmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) defines a spectrum of histological abnormalities, from simple fatty liver to nonalcoholic steatohepatitis (NASH), in a person consuming no alcohol (1)(2)(3)(4)(5)(6) (Table 1). NAFLD is a part of the metabolic syndrome, particularly in obesity, hyperlipidemia, and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) defines a spectrum of histological abnormalities, from simple fatty liver to nonalcoholic steatohepatitis (NASH), in a person consuming no alcohol (9,10,11). The main element of NAFLD is the accumulation of triglycerides (TG) as fat droplets within the cytoplasm of hepatocytes, which is a prerequisite for subsequent events of NASH, as more than 5%-10% of hepatocytes have fat droplets, as evident on liver biopsy (10).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of NASH related cirrhosis and hepatocellular carcinoma (HCC) is also high among patients with diabetes, as in obesity (13,14,16). As a risk factor, hypertriglyceridemia is also associated with insulin resistance and NAFLD, even in patients without obesity (11,23).…”
Section: Discussionmentioning
confidence: 99%
“…3 A communitybased cross-sectional study indicated that regular exercise was associated with a reduced risk of NAFLD. 8 The primary approach to treating NAFLD is the control of underlying risk factors (e.g. diabetes, hyperlipidemia, obesity and other comorbidities), and lifestyle modification through physical activity and dietary habits is a wellestablished therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%